Fixed-dose formulation of nifedipine and lidocaine for the treatment of anal fissures: results from a prospective, multicenter, single-arm and post-marketing observational study - Mysore, Rajasekhar; Ashok, Bhate Prasad; Anna, Nitin Bhople; Karankumar, Jejoe; Acharya, Shivani (International Journal of Research in Medical Sciences, 2025)
Background: Anal fissures are a common cause of severe anorectal pain and impaired quality of life, most often affecting individuals aged 15-40 years. Combination therapy with nifedipine and lidocaine has shown promise for symptom relief and healing, yet Indian clinical data remain scarce, highlighting the need for real-world evaluation of this fixed-dose combination (FDC). Methods: This prospective, multicenter, single-arm, open-label, post-marketing observational study evaluated the effectiveness and safety of FDC of nifedipine and lidocaine in Indian patients with acute or uncomplicated chronic anal fissures. The primary effectiveness endpoint was improvement in pain management. Secondary endpoints evaluated improvement in fissure healing, number of rescue medications required, global effectiveness and tolerability to therapy. Safety was evaluated by monitoring adverse drug reactions (ADRs). Results: Fifty patients (male: female, 39:11), with a mean (SD) age of 43.5 (16.1) years were enrolled. Pain intensity decreased significantly from a mean (SD) of 6.6 (0.8) at baseline to 3.7 (1.4) and 1.2 (1.5), respectively at week 3 and 6. At Week 6, 93.0% of patients achieved complete re-epithelialization, with no requirement for rescue medication. The treatment was well tolerated with no incident of ADRs. Conclusions: The study demonstrated statistically significant pain reduction along with improvements in fissure healing over 6 weeks of treatment with the FDC in Indian patients. The complementary actions of nifedipine and lidocaine contributed to both symptomatic relief and sustained healing, with no ADRs reported. These findings support its effectiveness, acceptability, and suitability as a non-surgical treatment option in routine clinical practice.